TRANSLATING CULTURE, RATHER THAN LANGUAGE: NARRATING THE (KOREAN) NATION IN OTHER LANGUAGE(S); (EXAMPLES OF CHANG REA LEE, EUNY HONG AND KRYS LEE) - ŠKVORC, Boris (International Journal of Korean Humanities and Social Sciences, 2021)
This article will concentrate on three major topics. The first one will be connected with the idea of globalization and universalism in relation to national cultural and literary canons. The second one will discuss the possibility of how the national language and literature can stay authentic and universal, that how it can remain simultaneously appreciated as a work of difference and an artefact of universal value. This calls for the introduction of the main topic which is the realm of translation, especially translation understood as a trans-creation, that is the re-creation of one literary world within (an)other cultural discourse, being it in a different language, or even uttered in a new lingua franca, which today is English. That means that the other nation can also be narrated in English, but in an English used by others for their own purposes, sometimes only commercial but other times purposely chosen as the tool of contra-hegemonic statement(s), having their own purposes and ways. How we can trans-create that in reading is of the utmost importance for interpretation. At the end of this essay we will see how that reflects on both the otherness of authentic culture (in this case study Korean) as well as English speaking discourse and English as an authentic language and the tool of trans-creating and disseminating the idea of literature as a global entity (or/and system).